“BRAINballs” educational balls - An innovative teaching method in education "Children learn while playing" - Han, Pham Van; Cichy, Ireneusz; Wawrzyniak, Sara; Rokita, Andrzej (VNU Journal of Science: Education Research; Vol 36 No 4DO - 10.25073/2588-1159/vnuer.4443, 2020)
The method of teaching using "BRAINballs" educational balls in physical education classes has been researched and widely applied to children of pre-schools and primary schools in Poland, with the aim of developing motor skills, improve physical development and academic achievement of students. In this article, we present an empirical pedagogical study using BRAINballs in teaching physical education classes to second grade students at primary schools in Vietnam. The purpose of the study was to examine changes in math skills, English and physical fitness in students from the experimental class compared to the control class at two times before and after the experiment. The results of this study will be the premise for further research to prove the effectiveness and suitability of BRAINballs when applied to teaching primary school students in Vietnam.